Extraction of DNA on human bone powder - Muhammad Edhil Akbar Bur; Muhammad Tasri Hidayat; Isna Rasdianah Aziz; Setia Betaria Aritonang (Genetikawan Muda Indonesia, 2021)
Bone is a dynamic network that has a complex cellular regeneration system. A forensic examination is closely related to examining the physiology and anatomy of the living body, including bone as the evidence in DNA testing. This study aims to analyze the DNA extraction on human bone powder using PrepFiler® BTA Forensic DNA Extraction Kit. DNA was isolated from compact and cancellous bone tissue from decomposed human bodies. The bones were soaked in NaOCl for 5 min, then rinsed with nuclease-free water. The bone was sawn into bone powder and then extracted using 220 µl of BTA lysis, 7 µl of Prot-K, and 3 µl of DTT. PrepfilerTM Lysis Buffer was added as much as 300 µl then homogenized by vortex and spin using a centrifuge. Spectrophotometry was performed to measure the DNA concentration using an absorbance from 230 nm to 320 nm. The results showed that the DNA purity values of the three samples of compact and cancellous bone powder used were close to good quality: 2.08, 2.06, and 1.71, respectively. Low concentration values obtained from compact bone samples were 14.2 ng/µL and 11.9 ng/µL respectively, which inversely proportional to cancellous bones by 59 ng/µL.